A comparative study of a new wireless continuous cardiorespiratory monitor for the diagnosis and management of patients with congestive heart failure at home. - Andrews, D; Gouda, MS; Higgins, S; Johnson, P; Williams, A; Vandenburg, M (2002)
Congestive heart failure (CHF) is a major and increasing chronic disease in Western society, with a high mortality, morbidity and cost for unplanned hospital admissions. Continuous cardiorespiratory monitoring is required to detect Cheyne-Stokes respiration (CSR). We have tested a new wireless monitoring system and compared it with polysomnography (PSG) and respiratory inductance plethysmography (RIP) in six CHF patients with CSR in a sleep laboratory. The wireless system compared well with RIP for the detection of CSR but less well with PSG, which had unexpected but significant respiratory sensing errors that led to misclassification of the respiratory disorder present. The wireless system could be used to select CHF patients for better-customized treatment at home as part of a specialist-supported community telemedicine programme.